편측성 하악 과두 골절 후의 교합 관계 회복 - 김유경; 박성호; 노병덕; Kim, Yoo-Kyung; Park, Sung-Ho; Roh, Byoung-Duck (Restorative dentistry & endodontics, 2012)
Complications resulting from condylar fracture include occlusal disturbance due to loss of leverage from temporomandibular joint (TMJ). In general, closed reduction with active physical training has been performed, and under favorable circumstances, adaptation occurs in attempt to restore the articulation. The patient in this case report had unilateral condylar fracture accompanied with multiple teeth injuries, but he was left without any dental treatment for 1 mon which led to unrestorable occlusal collapse. Fortunately, delayed surgical repositioning of dislocated maxillary anterior teeth followed by consistent long-term physical training has been proved successful. Normal occlusion and satisfactory remodeling of condyle were obtained on 10 mon follow-up. 본 증례의 편측성 하악 과두 골절 환자는 외상 후 1개월간 다수의 상악 전치부 치아 외상이 간과되어 교합이 붕괴된 상태로 내원하였다. 변위된 상악 전치부 치아들의 외과적 정복 후 지속적인 기능 운동을 진행하여, 10개월 후 정상 교합 및 하악 과두 골절부의 골유합이 확인되는 양호한 결과를 얻을 수 있었다.